Salvage Re-irradiation With Single-modality Interstitial Brachytherapy for the Treatment of Recurrent Gynaecological Tumours in the Pelvis: A Multi-institutional Study. Issue 1 (January 2020) - Raziee, H.; D'Souza, D.; Velker, V.; Barnes, E.; Taggar, A.; Mendez, L.; Leung, E.
Abstract: Aims: Recurrent gynaecological tumours can cause significant morbidity with limited salvage options. This study investigates the strategy of salvage single-modality interstitial brachytherapy (SM-ISBT) for recurrent gynaecological pelvic cancer at two specialised ISBT centres. Materials and methods: Patients who had received salvage SM-ISBT for pelvic recurrence of gynaecological cancers from September 2008 to January 2017 were included. None had distant metastasis at the time of recurrence. Local control, progression-free and overall survival and long-term toxicities were evaluated. Results: Twenty-six patients with a median follow-up of 24 months (range 2.5–106.3 months) after SM-ISBT were included. Primary cancer sites were endometrium (20), cervix (4), vulva (1) and vagina (1). All patients had prior whole-pelvic external beam irradiation and 16 had prior brachytherapy. The median disease-free survival prior to SM-ISBT was 20.3 months (interquartile range 9.9–30.5). SM-ISBT was delivered with high dose rate technique over three to six fractions. The median high-risk clinical target volume was 34.6 cm 3, with a median D90 of 29.1 Gy (range 16.1–64.6). The median bladder, rectum and sigmoid D2cm 3 were 15.5, 18.7 and 3.7 Gy, respectively. After SM-ISBT, complete and partial responses were achieved in 17 (64%) and 5 (19%) patients, respectively. Two (7.4%) patients had grade 3 toxicities (both vaginal stenosis), with no grade 4 complications. Eighteen patients (69%) recurred, including local, regional and metastatic in 14 (54%), 8 (30%) and 5 (19%) patients, respectively. Two-year local control, progression-free survival and overall survival were 50, 38 and 78%, respectively. In follow-up, 12 patients (46%) remained in local control. Conclusions: Salvage SM-ISBT re-irradiation for pelvic recurrence of gynaecological malignancies was feasible and safe. With limited salvage options, the local control obtained in more than a quarter of patients seems reasonable. Further efforts are needed to establish a consensus about the optimal patient selection, dose fractionation, implant technique and combination with systemic therapies. Highlights: Single-modality brachytherapy is feasible for salvage re-irradiation in pelvis for gynaecological cancers. It provides a 2-year local control of 50% and 2-year overall survival of 78%. Toxicity profile is acceptable, with 7% grade 3 and no grade 4 toxicities.